2020
DOI: 10.1038/s41386-020-00923-1
|View full text |Cite
|
Sign up to set email alerts
|

The renin–angiotensin system in PTSD: a replication and extension

Abstract: Prior observational studies have suggested that medications targeting the renin-angiotensin system, such as angiotensinconverting enzyme inhibitors (ACE-Is) and angiotensin receptor blockers (ARBs), may be associated with decreased PTSD symptoms. Given known sex differences in PTSD prevalence and cardiovascular disease, here we tested whether the effects of ACE-I/ARB status on PTSD differ by sex. We also expanded these observations with replication analyses in a large biorepository database. Participants in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Despite converging evidence emphasizing the role of hyperarousal and a negative memory encoding bias during trauma exposure for the development of PTSD, the underlying mechanisms have been difficult to target therapeutically [3,7,8]. Previous observational studies demonstrated that blockade of the RAS via LT during trauma exposure reduced the incidence of PTSD and hypothesized that the beneficial effects may be mediated by an LT-induced attenuation of autonomic reactivity or arousal [19,20]. In the present study LT did not affect subjective arousal experience while it slightly enhanced memory performance and abolished the memory advantage of negative material.…”
Section: Discussionmentioning
confidence: 99%
“…Despite converging evidence emphasizing the role of hyperarousal and a negative memory encoding bias during trauma exposure for the development of PTSD, the underlying mechanisms have been difficult to target therapeutically [3,7,8]. Previous observational studies demonstrated that blockade of the RAS via LT during trauma exposure reduced the incidence of PTSD and hypothesized that the beneficial effects may be mediated by an LT-induced attenuation of autonomic reactivity or arousal [19,20]. In the present study LT did not affect subjective arousal experience while it slightly enhanced memory performance and abolished the memory advantage of negative material.…”
Section: Discussionmentioning
confidence: 99%
“…However, in meta-analyses restricted to those studies that contributed medication-adjusted blood pressure values, we found similar results. Furthermore, previous studies have shown that certain classes of antihypertensive medications (e.g., angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers) are associated with lower PTSD symptoms in trauma-exposed individuals ( Khoury et al, 2012 ; Seligowski et al, 2021 ), and that the effects of these antihypertensive medications may be dependent on genetic liability ( Nylocks et al, 2015 ). Despite these limitations, our study has several strengths, including generating PGS from a large trans-ethnic GWAS of blood pressure, utilizing continuous measures of PTSD symptom severity, and conducting team science trans-ethnic meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Novel studies reported premature endothelial senescence in veterans and non-veterans with PTSD, indicating that BBB disruption likely plays a pivotal role in this disorder (Boscarino, 2008;Grenon et al, 2016;Thurston et al, 2018). Others have found that war veterans with PTSD, like older individuals, present with defective mitochondria, telomeres, furin/plasmin, and BDNF, connecting cerebral EC senescence with dysfunctional subcellular structures (Levin et al, 1997;Doughan et al, 2008;Gray and Ellis, 2008;Fleegal-DeMotta et al, 2009;Khoury et al, 2012;Grenon et al, 2016;Aksu et al, 2018;Connolly et al, 2018; Stein et al, 2018;Miranda et al, 2019;Seligowski et al, 2021;Cleveland et al, 2021).…”
Section: Furin Cleaving Site and Ptsdmentioning
confidence: 99%
“…Numerous studies have associated PTSD with the stress mediators of the hypothalamic-pituitary-adrenal (HPA) axis and autonomic nervous system, the two main drivers of stress related phenotypes. However, here we only discuss the SARS-CoV-2usurped renin-angiotensin system (RAS) that can also trigger this pathology (Chrousos and Zapanti, 2014;Griffin et al, 2014;Marinzalda Mde et al, 2014;Terock et al, 2019;Yu et al, 2019;Shkreli et al, 2020;Seligowski et al, 2021). Indeed, angiotensin receptor blockers (ARBs) and angiotensin converting enzyme inhibitors (ACEi) showed beneficial effects in both PTSD and severe COVID-19, suggesting that dysfunctional RAS may play an essential role in both conditions (Khoury et al, 2012;Marvar et al, 2014;Vian et al, 2017).…”
Section: Introductionmentioning
confidence: 99%